PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - DINI MARTINDA LESTARI; ANDI HASRYNINGSIH ASFAR (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2020)
The background of this study is tax avoidance at various industrial sector tend to fluctuation thought to be caused unstable Profitabilitas and firm size.The objective of this research to determine about influence profitabilitas dan firm size partial dan simultaneously toward tax avoidance at various industrial sector company period 2015-2018.The population of this study were 46 listings and manufacturing company listed on the Indonesia Stock Exchange (BEI) period 2015-2018. With used purposive sampling method acquired 40 samples. Multiple regression analys is used in this study to see the effect of the independent variable on the dependent variable either jointly or individually. The results of research that hypothesis test showed Profitabilitas toward tax avoidance tcount > t table (2.644 > 2.02) is mean have influence. Firm size toward tax avoidance tcount > t table (0.443 > 2,02) is mean have influence. While Profitabilitas and Firm Size toward tax avoidance Fcount > F table (4.667 > 3,24) is mean have influence.Partial result of the study there is a significant influence between profitbeabilitas toward tax avoidance and there not a significant influence between Firm size toward tax avoidance. While simultaneously there is a significant influence between profitabilitas and firm size toward tax avoidance.